Library Interior Design for Digital Native Generation - ., Felecia; Halim, Siana; Tulistyantoro, Lintu; Wulandari, Dian (KnE Life Sciences, 2020)
Digital native held information in their hands through the gadget. Previous research to 460 respondents in six university libraries in Surabaya, Indonesia shows that overall quality of the library is excellent. However, it does not encourage them to come to the library. Therefore, library needs to facilitate digital native needs by repositioning as a community hub, a place where community interact, collaborate and learn. The library can also apply a hybrid library concept by adding digital collection through subscription or repository. Findings from previous research show that there are facilities need to be prioritized to encourage digital native to come: common rooms, discussion rooms, and books that support students’ academic needs. These facilities are re-arrange as a new library interior design. The method used to redesign the libraries are by conducting an interview with the users and questionnaires. It is found that each library visitors have different characteristic and preference, therefore the interior must be designed to accommodate those need. Keywords: Community hub; digital-friendly library; library attractivity